1994
DOI: 10.1159/000236807
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Murine Model of Allergic Pulmonary Inflammation

Abstract: Pulmonary inflammation with eosinophil (EOs) infiltration is a prominent feature of allergic respiratory diseases such as asthma. In order to study the cellular response during the disease development, an animal model of IgE-mediated pulmonary inflammation with characteristic eosinophilia is needed. We developed a method for inducing severe pulmonary eosinophilia in the mouse and also studied the numbers of EOs in blood and bone marrow and the response to corticosteroid treatment. Animals were sensitized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
165
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(178 citation statements)
references
References 12 publications
13
165
0
Order By: Relevance
“…Since allergic asthma has many hallmarks of a T H 2-type response in humans and in animal models, we tested whether ITK may be involved in the allergic inflammatory response in the lung to the model allergen OVA in a murine model of allergic asthma. In this model, mice are primed with OVA, then challenged IN with OVA (42). This treatment results in increased inflammatory cell infiltration into the lung, thickening of the epithelial cells lining the bronchioles of the lung, mucous secretion, and increases in IgE in the serum of these mice.…”
Section: Itk Null Mice Exhibit Reduced Lung Inflammation Following Almentioning
confidence: 99%
“…Since allergic asthma has many hallmarks of a T H 2-type response in humans and in animal models, we tested whether ITK may be involved in the allergic inflammatory response in the lung to the model allergen OVA in a murine model of allergic asthma. In this model, mice are primed with OVA, then challenged IN with OVA (42). This treatment results in increased inflammatory cell infiltration into the lung, thickening of the epithelial cells lining the bronchioles of the lung, mucous secretion, and increases in IgE in the serum of these mice.…”
Section: Itk Null Mice Exhibit Reduced Lung Inflammation Following Almentioning
confidence: 99%
“…On days 14, 24, 25, and 26, mice were challenged intranasally with 100 g of OVA in 0.1 ml of normal saline. In protocol B, mice were immunized on days 0 and 5 with 8 g of OVA in alum (1:1 in alum in 0.1 ml), as described earlier (23). On day 12, mice received 100 g of OVA in 0.1 ml of normal saline.…”
Section: Mouse Models Of Airway Allergic Inflammationmentioning
confidence: 99%
“…Therefore, we examined whether the requirement for CCR8 to affect the outcome of airway inflammation was masked by the dosage and timing of Ag challenge. In protocol B, mice were immunized with lower doses of Ag, as described previously (23). CCR8 Ϫ/Ϫ mice and WT littermates were sensitized on days 0 and 5 with 8 g of OVA, and later challenged with a single intranasal dose of OVA on day 12.…”
Section: Effect Of Ag Dose On Allergic Airway Inflammation In Ccr8 ϫ/mentioning
confidence: 99%
“…[5][6][7][8][9][10] However, these responses have typically been assessed in isolation from each other. We have recently demonstrated that C57BL/6J mice undergo a biphasic response to aerosolized ovalbumin (OVA) exposure.…”
mentioning
confidence: 99%